PTU-035 Economic impact of non-response to ursodeoxycholic acid in primary biliary cholangitis patients. (June 2019) - Sharma, Parivrudh; Crighton, Lynne; Vijayan, Balasubramaniam; English, Shirley; Mukhopadhya, Ashis
Abstract : Introduction: NICE recommends the use of Obeticholic acid (OCA), as a second-line treatment for failed or intolerant ursodeoxycholic acid (UDCA) drug therapy in primary biliary cholangitis (PBC). This audit aims to determine the proportion of PBC patients, in a tertiary referral hospital experiencing failed UDCA drug therapy, to gauge the potential economic impact of a switch to OCA. Methods: A total of 120 patients with PBC were identified from an existing patient database. 24 patients were excluded due to inappropriate diagnosis, missing data, non-attendance or failure to tolerate UDCA. Baseline characteristics, UDCA dosage and biochemical response were recorded for all patients. For the purpose of this study, failed UDCA drug therapy was defined as an alkaline phosphatase (ALP) level of greater than 1.67 times the upper limit of normal (ULN) (Toronto Criteria) 1 . Results: Of the 96 patients included for analysis, 9 were male and the remaining 87 were female. The mean age and weight were 64.4± 11.9 years and 75.9± 15.4 kg respectively. The mean blood results for haemoglobin, platelets, bilirubin, ALP, alanine aminotransferase, and creatinine were 126.8± 15.0 g/L, 254.5± 94.3 x10^9/L, 9.4± 4.3 µmol/L, 144.4± 75.6 u/L, 30.3± 19.3 u/L, and 75.1± 28.3 µmol/L respectively. The mean UDCA dose for the cohort was 13.9± 5.9 mg/kg/day. Biochemical failure was documented in 13 patients who had an ALP of greater than 1.67 times the ULN at the end of 1 year of therapy with UDCA (13.5%). Of these 13 patients, 4 were found to be on suboptimal dosage of UDCA (<10 mg/kg/day), leading to a true non-response rate in 9/96 subjects (9.4%). The annual cost of UDCA at NHS Grampian is £ 191.90 per patient and £ 14, 813.28 for OCA. Shifting these non-responsive patients to OCA would accrue recurring annual expenditure of £ 131, 592.42. Conclusions: A substantial proportion of PBC patients were found to be biochemically unresponsive to UDCA. Shifting these patients to OCA would lead to significant drug expenditure for NHS Grampian. An intermediary step of shifting non-responsive patients to the cheaper drug, Bezafibrate, may prove to be cost-effective, but this drug has been revealed to have no benefit in a recent Cochrane review 2 . References: Kumagi T, Guindi M, Fischer SE, et al. Baseline ductopenia and treatment response predict long-term histological progression in primary biliary cirrhosis. Am J Gastroenterol 2010; 105: 2186–2194. Rudic JS, Poropat G, Krstic MN, Bjelakovic G, Gluud C. Bezafibrate for primary biliary cirrhosis. Cochrane Database of Systematic Reviews 2012, Issue 1. Art. No.: CD009145.